2020
DOI: 10.1080/03088839.2020.1721584
|View full text |Cite
|
Sign up to set email alerts
|

Exploring effects of ship traffic characteristics and environmental conditions on ship collision frequency

Abstract: This study aims to model the complex relationship among the traffic characteristics (i.e., traffic flow, traffic speed, traffic density), environmental conditions (i.e., darkness condition, weather condition and traffic lane width) and ship collision frequency in Yangtze River estuary water areas. Considering the effects of ship approach angle, relative speed, ship type and darkness condition on the ship collision avoidance capability, a dynamic ship domain model has been presented to measure ship collision fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…The validation method is in line with previous study results (Zhang et al, 2015). The high-density distribution of NACEs is similar to previous studies in the region (Weng et al, 2020) study, as shown in Figure 10(b). Therefore, the identified NACEs are reliable and useful for analysis.…”
Section: Naces Validationsupporting
confidence: 91%
See 1 more Smart Citation
“…The validation method is in line with previous study results (Zhang et al, 2015). The high-density distribution of NACEs is similar to previous studies in the region (Weng et al, 2020) study, as shown in Figure 10(b). Therefore, the identified NACEs are reliable and useful for analysis.…”
Section: Naces Validationsupporting
confidence: 91%
“…The ship flow analysis is a powerful tool for studying the channel efficiency, ship characteristics and ship accident types in small areas. In the Yangtze Estuary, some cross-section analysis has been used for research (Chai et al., 2020; Weng et al., 2020), and the ship characteristics of its research waters have been further defined. To further understand the relationship between NACEs and tidal changes, we conducted the cross-sectional analysis of Wusong, Nancao waterway and Zhoushan.…”
Section: Discussionmentioning
confidence: 99%
“…Since dynamic information is automatically updated based on sensor data, it is susceptible to faults and errors, similar to those described in section 3.1.1. In addition, problems may occur even in the process of collecting and transmitting data between AIS stations, as noted by Weng et al (2020). The AIS signal can also be influenced by external factors, such as weather conditions and Earth's magnetic field, due to their interference with the very high frequency (VHF) equipment.…”
Section: Ais Datamentioning
confidence: 99%
“…Moreover, the receiving station has a short time slot during which the data must be received, and due to heavy traffic in the region, it fails to receive the data from all the ships in that time. In some cases, small ships deliver inaccurate information due to incorrectly calibrated transmitters, as shown by Weng et al (2020). In a case study, Harati-Mokhtari et al (2007) observed that 2% of the MMSI (Maritime Mobile Service Identity) information was incorrect and 30% of the ships were not properly marked with the correct navigation status.…”
Section: Ais Datamentioning
confidence: 99%
“…In China's Yangtze River and its estuary, more than 100,000 ships pass through the estuary area each year. The rapid growth of ship density, overtaking, and encounters of surface ships may lead to higher ship accident rates [5]. In addition, serious ship collision accidents may lead to disastrous consequences [6].…”
Section: Introductionmentioning
confidence: 99%